a)
[tex] \sqrt{ {3}^{2} } = \sqrt{9} = 3[/tex]
[tex] \sqrt{( - 3 {)}^{2} } = \sqrt{9} = 3[/tex]
[tex] \sqrt[3]{ {3}^{3} } = \sqrt[3]{27} = 3[/tex]
[tex] \sqrt[3]{( - 3 {)}^{3} } = \sqrt[3]{ - 27} = - 3[/tex]
b)
[tex] \sqrt{ {7 }^{2} } = \sqrt{49} = 7[/tex]
[tex] \sqrt{( - 7 {)}^{2} } = \sqrt{49} = 7[/tex]
[tex] \sqrt[3]{ {2}^{3} } = \sqrt[3]{8} = 2[/tex]
[tex] \sqrt[3]{( - 2 {)}^{3} } = \sqrt[3]{ - 8} = - 2[/tex]
c)
[tex] \sqrt{ {12}^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt{( - 12 {)}^{2} } = \sqrt{144} = 12[/tex]
[tex] \sqrt[3]{ {10}^{3} } = \sqrt[3]{1000} = 10[/tex]
[tex] \sqrt[3]{( - 10 {)}^{3} } = \sqrt[3]{ - 1000} = - 10[/tex]